Throughput enhancement of IEEE 802.11n/ac in different environments using physical isolation and antenna sophistication approaches / Rabbil Atul Hadawiah Che Yusoff - Che Yusoff, Rabbil Atul Hadawiah (2016)
One of the major issues in WLAN is the changes of physical environment and the best technology is not the latest one for indoor or outdoor environment installation. The signal strength can be reducing over distance and across or through radio frequency obstructions and it is not clear if the high-predicted throughputs are achievable even in the absence of interference. Objectives for this research are to design an approaches to enhance throughput of wireless network IEEE802.11n/ac in different environments, to implement physical isolation and antenna sophistication approaches in both IEEE 802.11n/ac and to evaluate performance analysis of wireless network IEEE802.11n/ac in an indoor and outdoor environments. This research have been implement wireless network IEEE802.11n/ac testbed in the indoor and outdoor environment with network benchmarking tools like Jperf-2.0.2 to obtain all data needed. Throughput will be measured as the experiment run on both technologies. The results show that 802.11ac is much better than 802.11n in both environments. Hence, by implementing these two approaches, it can reduce the loss of throughput. These performance improvements are sensitive to channel conditions, with the achieved data rates rapidly declining as the distance between the transmitter and the receiver is increased. An approach is proven can enhance throughput in the indoor and outdoor environments.